A first-principle study of Os-based compounds: Electronic structure and vibrational properties. (September 2016) - Arıkan, N.; Örnek, O.; Charifi, Z.; Baaziz, H.; Uğur, Ş.; Uğur, G.
Abstract: The electronic structure, elastic, and phonon properties of OsM (M=Hf, Ti, Y and Zr) compounds are studied using first-principles calculations. Elastic constants of OsY and specific heat capacity of OsM (M=Hf, Ti, Y, and Zr) are reported for the first time. The predicted equilibrium lattice constants are in excellent agreement with experiment. The calculated values of bulk moduli are considerably high but are much smaller than that of Osmium, which is around 400 GPa. The phase stability of the OsM (M=Hf, Ti, Y and Zr) compounds were studied by DOS calculations and the results suggest that OsY is unstable in the B2 phase. The brittleness and ductility properties of OsM (M=Hf, Ti, Y and Zr) are determined. OsM (M=Hf, Ti, Y and Zr) compounds are predicted to be ductile materials. The electronic structure and phonon frequency curves of OsM (M=Hf, Ti, Y and Zr) compounds are obtained. The position of Fermi level of these systems was calculated and discussed in terms of the pseudo gaps. The finite and small DOS at the Fermi level 0.335, 0.375, 1.063, and 0.383 electrons/eV for OsHf, OsTi, OsY, and OsZr, respectively, suggest that OsM (M=Hf, Ti, Y and Zr) compounds are weak metals. Highlights: We present electronic and phonon band structure of OsM (M=Hf, Ti, Y and Zr). Elastically, all the compounds have been found to be stable. OsM (M=Hf, Ti, Y and Zr) exhibit metallic characters. Elastic constants of OsY and specific heat capacity of OsM (M=Hf, Ti, Y and Zr) calculated using first principles is reported for the first time.